A new discrete information model and its applications for the study of contingency tables. (3rd April 2022) - Parkash, Om; Singh, Vikramjeet; Sharma, Ratneer
Abstract: There exists an assortment of parametric and non-parametric discrete and continuous information models but still inevitability arises to enlarge supplementary parametric models to induce flexibility in the system under study. Moreover, there appears well-built relation between information entropy and the field of statistics. The present communiqué deals with the proposal of a new discrete information entropy model along with its applications in statistics. By employing the newly developed entropy model, we have enriched the application region of maximum entropy principle after the learning of contingency tables recurrently employed in statistics.